Development and properties of light-transmitting concrete (LTC) – A review. (15th February 2021) - Chiew, Shing Mei; Ibrahim, Izni Syahrizal; Mohd Ariffin, Mohd Azreen; Lee, Han-Seung; Singh, Jitendra Kumar
Abstract: The consumptions of artificial light especially in urban area leads to carbon footprints and global warming. The introduction of light-transmitting concrete (LTC) enables light to be transmitted through opaque concrete and reduces building energy consumptions. The aesthetic value and the light transmittance properties of LTC attracted the attention among researchers on the investigations and development of this type of concrete. However, the application of LTC in construction industry is still immature due to several reasons including intensive labour cost and complexity of the manufacturing process, insufficient reliable data on the mechanical properties and durability, as well as the lack of design modelling. This paper reviewed the types of LTC as well as the research findings regarding the mechanical properties, durability, microstructure analysis as well as the light transmittance properties. This paper also critically discussed the assessment, design modelling, theoretical studies and cost analysis of LTC based on various parameters. LTC was proven to reduce the total energy consumptions of a building significantly. More investigations are required to examine the light transmitting properties and durability of LTC especially when exposed to the various environmental conditions. Highlights: Detailed review on the types of LTC, its properties, applications and development. Critical discussion on mechanical strength and light transmittance of LTC. Simulation modelling and theoretical studies of LTC are reviewed. Manufacturing cost and total energy expenditure of LTC are discussed. Suitability and durability of LTC should be more focused in future research.